Milking systems and colostrum handling as an agent for the spread of poliarthritic Streptococcus dysgalactiae strains in sheep farms: case report - Álvaro Cañete-Reyes; Jorge Gutiérrez González; Lauren V. Alteio; David Rodríguez-Lázaro; Marta Hernández (BMC Veterinary Research, 2025)
Abstract Background Streptococcus dysgalactiae is the main cause of neonatal polyarthritis in sheep and is also an important agent in ovine mastitis. However, the main sources of contamination by this pathogen have not been studied in depth. Case presentation A polyarthritis outbreak in 2-3-day-old lambs with an incidence rate of approximately 40%, was reported in a sheep farm focused on sheep’s milk and lamb’s meat. The problem persisted over three consecutive lambing cycles. The pathogen was identified as S. dysgalactiae by 16 S rRNA sequencing of joint fluid. Its genome was isolated and sequenced as S. dysgalactiae MLST 454. The main antibiotic resistance genes and virulence factors were determined. The water supply, milking system, and pasteurisation efficiency were tested by standard plate count methods as well as 16 S rRNA sequencing techniques. High levels of contamination were found in the milking system and colostrum, with the presence of Streptococcus spp. and S. dysgalactiae. The implementation of enhanced pasteurization and more rigorous decontamination of the milking system were sufficient to control the problem on the farm. Conclusions This study reveals the role of the milking system contamination in facilitating the spread of bacteria, such as S. dysgalactiae and provides evidence for the existence of an oral pathway of infection via colostrum.